Methodological issues of developmental psychology in professors historical heritage of traditional universities of Ukraine - Vlasovа, O.; Власова, О. (Київський національний університет імені Тараса Шевченка, 2018)
In the article the author vision of the relevance and importance of "rediscovery" of scientific and psychological legacy of traditional universities professors Ukraine – period of the nineteenth century. It is shown that the formation of modern national methodology of psychology as an independent branch of psychological and pedagogical knowledge has profound scientific, psychological and philosophical roots in the research of scientists oldest universities in Ukraine (Kharkiv, Kyiv and Odessa). Their works were in the origins of scientific psychology and national psychology schools recognized not only in Ukraine, but Russian Empire, of which at that time was all Ukrainian science.

У статті представлене бачення автором актуальності та значення "перевідкриття" науково-психологічної спадщини професорів класичних університетів України періоду ХІХ–ХХ ст. Показано, що становлення методології сучасної вітчизняної психології розвитку як самостійної галузі психолого-педагогічного знання має глибоке науково-психологічне та філософське коріння в дослідженнях науковців найстаріших університетів України (Харківського, Київського та Одеського). Їх роботи стояли у витоків виникнення наукової психології та визнаних національних психологічних шкіл не лише України, а й всієї Російської імперії, частиною якої на той час була вся українська наука.
Актуальні питання психології розвитку в історичній спадщині науковців українських класичних університетів
Keywords: національні психологічні школи; методологія; психологія розвитку; теоретична психологія; експериментальна психологія; комплексний метод; генетичний підхід; national psychological school; methodology; developmental psychology; theoretical psychology; experimental psychology; complex method; genetic approach